Feasibility Study Economic Development of Divari Medical Center (DMC) Hospital - Rosita (Kusuma Negara Business School, 2021)
The general purpose of this Feasibility Study is to conduct a physical and economic feasibility study on the plan to upgrade the status of the Divari Medical Center (DMC) Clinic to a Class D Primary Hospital in West Manokwari District, Manokwari Regency, West Papua Province. Specifically, it aims to analyze the economic feasibility of the plan to upgrade the status of the Divari Medical Center (DMC) Clinic to a Class D Primary Hospital. Data was collected through field research to obtain primary and secondary data. Data analysis and processing is carried out in stages (a) structuring, classifying, compiling, and tabulating data referring to the results of literature studies, field surveys and interviews conducted, (b) analyzing economic feasibility studies including investment plans and sources of funds, projections income and costs, Cash Flow projections, Break Event Point (BEP) values, Internal Rate of Return (IRR) values, and Net Present Value (NPV) values, (c) formulating study results in the form of economically feasible or not. Based on the results of financial analysis through NPV, PP, IRR and BCR as well as BEP, that the investment plan for the development of the Divari Medical Center (DMC) Clinic into a Class D Pratama Hospital is economically feasible.